IN VITRO ANTI-INFLAMMATORY MECHANISM OF FOLIUM HIBISCI MUTABILIS LEAVES ETHANOL EXTRACTS - Wang, Jiangning; Li, Xiaorong; Gao, Lei; Wang, Xueyan (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
Background: Folium Hibisci Mutabilis was one of the traditional Chinese medicines with pharmacological activities of wound healing, antibacterial and anti-inflammatory, normally applied to the clinical treatment of local purulent infection, scald, and epidemic parotitis. However, few people reported that its effects of extracts on RAW264.7, cells and TNF-α, IL-6, and NO levels in rats serum of inflammation rats. Materials and Methods: We mainly adopted the RAW264.7, macrophage cell line which was intervened by lipopolysaccharide (L PS), to establish the model of inflammatory cells. The secretion changes of TNF, and IL-6, level in the model cell acted by the FHMAEs, were detected by ELISA, NO level changes were determined by nitrate reductase method; Arthritis model induced by Collagen Type II were chose, and regulatory role of FHMAEs on IL-6 and NO level in serum were observed, FHMAEs mechanism of action were investigated in the treatment of rheumatoid arthritis. The states of the model rats were recorded. Results: Release of TNF-α, IL-6, and NO in LPS-induced RAW264.7, cells were significantly inhibited and has a clear dose-response relationship; The TNF-α, IL-6 and NO levels were reduced by FHMAEs in experimental arthritis rats serum, and the status of rats were improved. At last, we found that IL-6, NO and TNF-α levels in the inflammatory cells could be reduced by FHMAEs greatly. Conclusion: Both synovial inflammation and synovial proliferation could be reduced or inhibited by FHMAEs, all of this may provide experimental effective data for the novel drugs development and the clinical treatment of rheumatoid arthritis.